Chemical composition, anti-microbial, anti-inflammatory and cytotoxic activity of essential oils from Melicope pteleifolia (Champ. ex Benth.) T.G.Hartley leaves and stems collected in Lam Dong province - Trịnh, Thị Điệp (2023)
The essential oils extracted by hydrodistillation from the leaves and stems of M. pteleifolia collected in Bidoup-Nui Ba National Park, Lam Dong province, Vietnam were investigated for their chemical composition and bioactivity. 29 compounds were identified in the leaf oil (MPL), of which trans-α-bergamotene (41.1%), followed by trans-γ-bisabolene (13.0%), linalool (7.6%), and β-atlantol (7.3%) were the most abundant. The stem oil (MPS) contained 21 identified constituents, mainly trans-α-bergamotene (63.7%), limonene (7.4%), and linalool (7.1%). MPL exhibited inhibitory effects on S. aureus, B. subtilis, and L. fermentum, while MPS significantly inhibited the growth of S. aureus, B. subtilis, E. coli, and C. albican and showed minimal inhibition against three other bacteria. MPL inhibited NO production in macrophage RAW 264.7 cells (IC50 19.86 ± 0.16 g/mL). Both MPL and MPS showed significant cytotoxic effects on all three tested cell lines SK-LU-1, MCF-7, and HepG2 with the IC50 values of 20.80 ± 1.42, 25.90 ± 1.47, and 23.42 ± 1.78 g/mL (for MPL) and 25.36 ± 2.41, 46.46 ± 3.13, and 47.41 ± 2.91 g/mL (for MPS), respectively. Their antifungal, anti-inflammatory, and cytotoxic activity were evaluated and reported for the first time.